2019
DOI: 10.1080/24759651.2019.1688604
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up challenges and requirement of technology-transfer for cyanobacterial poly (3-hydroxybutyrate) production in industrial scale

Abstract: Herwig (2019) Scale-up challenges and requirement of technology-transfer for cyanobacterial poly (3-hydroxybutyrate) production in industrial scale,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…254 PHAs can even be made from CO 2 in a marine setting without the requirement of any productive land. 255 Polybutylene succinate (PBS), poly (butylene adipate-co-terephthalate) (PBAT), polyvinyl alcohol (PVA), polyglycolic acid (PGA), and polycaprolactone (PCL) are the biodegradable polymers synthesized from petrochemical hydrocarbons. 255 For the purpose of developing the interior body panels of cars, Dorez 256 produced PBS-based composites by including natural fibers and ammonium polyphosphate (APP) as a fire retardant.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…254 PHAs can even be made from CO 2 in a marine setting without the requirement of any productive land. 255 Polybutylene succinate (PBS), poly (butylene adipate-co-terephthalate) (PBAT), polyvinyl alcohol (PVA), polyglycolic acid (PGA), and polycaprolactone (PCL) are the biodegradable polymers synthesized from petrochemical hydrocarbons. 255 For the purpose of developing the interior body panels of cars, Dorez 256 produced PBS-based composites by including natural fibers and ammonium polyphosphate (APP) as a fire retardant.…”
Section: Applicationsmentioning
confidence: 99%
“…255 Polybutylene succinate (PBS), poly (butylene adipate-co-terephthalate) (PBAT), polyvinyl alcohol (PVA), polyglycolic acid (PGA), and polycaprolactone (PCL) are the biodegradable polymers synthesized from petrochemical hydrocarbons. 255 For the purpose of developing the interior body panels of cars, Dorez 256 produced PBS-based composites by including natural fibers and ammonium polyphosphate (APP) as a fire retardant. By adding phosphorylation to natural fibers and heat hydrolysis to PBS, the APP enhanced the fire reserve property when exposed to fire, establishing a barrier layer over the composite.…”
Section: Applicationsmentioning
confidence: 99%
“…Smetana et al [30] showed that for Arthrospira platensis, replacing an open raceway reactor with a tubular design decreases half of the system impact. On the other hand, the use of outdoor cultivation, which can reduce the impact caused by artificial lighting, could reduce productivity due to fluctuations in light availability [44].…”
Section: Laboratory-scale Profile (20 L)mentioning
confidence: 99%
“…CCALA192 cultivated in 200 L volume [23], a randomly mutated strain of Synechocystis sp. PCC6714 cultivated in 40 L volume [24], Synechococcus leopoliensis cultivated in 200 L volume [25],…”
Section: Introductionmentioning
confidence: 99%